Outdoor Study Based Project Based Learning In Improving Students’ Collaboration At SMK.N 2 Malang - Putri Khansa Mudhiah; Laili Hidayati (Universitas Negeri Padang, 2026)
This study aims to examine the implementation of Project Based Learning (PjBL) based on outdoor study in improving the teamwork skills of tenth-grade Culinary students at SMKN 2 Malang. The study was motivated by the students' low level of teamwork skills, as indicated by limited active participation, ineffective communication, and unequal task distribution during group activities. This research employed a field research method using a descriptive qualitative approach. The participants consisted of nine students who took part in a fun cooking activity at SDN Dinoyo 4 Malang. Data were collected through observations, interviews, and documentation, while data analysis was conducted using the stages of data reduction, data display, and conclusion drawing. The findings showed that all participants demonstrated improvements in their teamwork skills during the implementation of PjBL based on outdoor study. These improvements were reflected in increased active participation, more effective communication, greater responsibility for assigned tasks, mutual assistance, respect for others' opinions, and stronger group cohesion. The findings indicate that PjBL based on outdoor study provides meaningful and contextual learning experiences that support the development of students' teamwork skills.